Polish motifs in the life of Mikhail Heller - Piekara, Jędrzej (Lodz University Press, 2021)
The book is a result of several years of studies on the life and work of Mikhail Heller – a historian of Jewish origin born in the Soviet Union, an emigrant who is particularly closely related to Poland, Polish emigration institutions and Poles in this country and abroad. Mikhail Heller, through his personal, formal and scientific relations, was one of the few Russians for whom Poland – both contemporary to him and the one from pages of history – was not one of the potential Russian territories but a great centre of Latin civilization, rich in culture and history, the only country Russia was so closely connected with. Heller used to say that “the only history of Russia that we are able to write about is the Russian-Polish history” and believed that the normalization of relations between Poles and Russians should be one of the most important goals of both emigrations after the World War II. It was the idea of reconciling of Poland and Russia that has been the main object of interest for Heller, next to the critique of communism, for the thirty years that he spent in exile in France. He was associated with two Polish emigration centres: Jerzy Giedroyc Literary Institute and Andrzej Stypułkowski Overseas Publications Interchange. He found close friends in the Polish environment, especially Józef Czapski, whom he considered to be the most outstanding representative of the “silver age”, combining the ideal features of a Russian, a Pole and a European. Mikhail Heller, a relentless anti-communist, a dedicated critic of "perestroika" and Mikhail Gorbachev, a researcher on the subject of “homo sovieticus”, a talented historian, a literary scholar and chronicler-journalist, documenting the reality of the Soviet Union with his pen sharpness, was a great friend of Poland and this book’s aim is to tell the story of this friendship.